Gambaran Motivasi Belajar pada Siswa Pengguna Smartphone di SMP Negeri 4 Garut - Sri Yekti Widadi; Inge Ajeng Pramudita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this research is to find out the description of learning motivation in smartphone users in SMP Negeri 4 Garut. The research method in this research is to use a descriptive research method. The results of the study half of the students (50.6%) rarely use smartphones and almost half the students (41.6%) have enough motivation to learn in SMP Negeri 4 Garut. Conclusion, Students who rarely use smartphones have sufficient learning motivation and students who often use smartphones have less learning motivation. Keywords: Learning Motivation, Smartphone Use